The effects of neutron irradiation and low temperature annealing on the electrical properties of highly doped 4H silicon carbide - Almaz, E.; Stone, S.; Blue, T.E.; Heremans, J.P. (My University, 2010)
The effects of neutron irradiation on the electrical properties of highly doped 4H SiC were studied. The material was fabricated into standard Hall bars for characterization of the material's resistivity, free-carrier concentration and electron Hall mobility as a function of 1 MeV equivalent neutron fluence in SiC (?1MeV,SiCEq). The post-irradiation effects of low temperature (175 °C) annealing on the same properties were also investigated. It was found that: (1) the material's resistivity doubled for ?1MeV,SiCEq=2. 7×1016cm-2, (2) the resistivity recovered (i.e. decreased) by only 81% from its post-irradiation values after 2 h of annealing, (3) the carrier concentration decreased linearly with ?1MeV,SiCEq with a carrier removal rate of 48.5±6.3 cm-1, (4) within experimental uncertainty, the carrier concentration recovered to its pre-irradiation values after 2 h of annealing, (5) the Hall mobility decreased linearly with ?1MeV,SiCEq with a mobility damage constant of (1.49±0.2)10-19 V s and (6) the Hall mobility was further degraded (i.e. decreased) by annealing. The mobility was found to decrease from its post-irradiation value by 27±8% after 2 h of annealing. © 2010 Elsevier B.V.
Keywords: Annealing; Hall effects; Neutron irradiation; Silicon carbide